Clinical reasoning assessment methods in prelicensure undergraduate nursing education : A scoping review - Li Sze, Chai; Lily, Lim; Muhamad Saiful Bahri, Yusoff; Azlina, Yusuf (Elsevier Ltd., 2025)
Aim: To identify and characterise clinical reasoning assessment methods in prelicensure undergraduate nursing education, highlighting their key features and applications. Background: Developing clinical reasoning is a core expectation in nursing education but poses significant challenges due to its cognitive complexity. Effective assessment approaches are critical for supporting student development and understanding this process. In resource-limited settings, where access to advanced technologies is limited, identifying adaptable methods is essential. However, assessment methods in this area remain underexplored. Design: Scoping review. Methods: Following Joanna Briggs Institute methodology and PRISMA-ScR guidelines, a comprehensive search was conducted in EBSCO Host (CINAHL, MEDLINE), ScienceDirect, Web of Science, Epistemonikos and ProQuest Dissertations and Theses. The review included primary studies reported on clinical reasoning assessment methods for prelicensure nursing students, focusing on measurable outcomes in quantitative or mixed-method studies. Data were extracted using a structured guide and analysed using descriptive qualitative techniques. Results: This review included 283 studies employing six primary response formats across diverse settings. Considerable variation was found in sample sizes, construct definitions, stimulus formats, scoring approaches, answer key development and rater characteristics. These findings illustrate the complexity of clinical reasoning assessment and underscore the need for standardisation to enhance consistency and comparability. Conclusion: This review maps the diversity of clinical reasoning assessment methods and identifies key areas for further research. It provides a foundation for evaluating the effectiveness, validity and feasibility of these strategies to support evidence-based, contextually adaptable practices in nursing education.